Enhancement‐Mode Field‐Effect Transistors and High‐Speed Integrated Circuits Based on Aligned Carbon Nanotube Films. (27th August 2021) - Lin, Yanxia; Liang, Shibo; Xu, Lin; Liu, Lijun; Hu, Qianlan; Fan, Chenwei; Liu, Yifan; Han, Jie; Zhang, Zhiyong; Peng, Lian‐Mao
Abstract: Aligned carbon nanotube (A‐CNT) films are expected to be an ideal channel material for constructing field‐effect transistors (FETs) that outperform conventional transistors, and multiple methods are developed to fabricate A‐CNT films with high semiconducting purity, good alignment, and high density. However, the reported A‐CNTs‐based FETs are almost all depletion‐mode FETs and suffer from poor subthreshold swing (SS). In this study, enhancement‐mode (E‐mode) FETs based on A‐CNT films are fabricated by systematically optimizing the channel material and CNT/high‐k/metal gate stack. The carrier mobility in top‐gate A‐CNT FETs reaches a maximum value of 1850 cm 2 V −1 s −1, which is near that of chemical‐vapor deposition grown individual CNTs and sets a record among A‐CNT films. The fabricated 200 nm‐gate length p‐type A‐CNT FETs present a SS of 73 mV dec −1, the transconductance of 1 mS µm −1, and an on‐current of 1.18 mA µm −1 at a bias of ‐1 V, indicating a real performance exceeding that of commercial Si‐based transistors at a similar gate length. Based on the high‐performance and uniform E‐mode FETs, ring oscillators with stage numbers 5, 7, 9, and 11 are fabricated with an optimized design and high yield, exhibiting a record propagation gate delay of 11.3 ps among CNT‐ and other nanomaterial‐based ICs. Abstract : Although field‐effect transistors (FETs) based on aligned carbon nanotube (A‐CNT) films are demonstrated, the depletion‐mode and poor subthreshold swing bring difficulty in constructing integrated circuits. The gate stack is systematically optimized and enhancement‐mode p‐type A‐CNT FETs are fabricated. The FETs present a real performance exceeding that of commercial Si‐based transistors at a similar gate length.